2021
DOI: 10.1186/s12889-021-12176-8
|View full text |Cite
|
Sign up to set email alerts
|

Mortality differences between migrants and Italians residing in Rome before, during, and in the aftermath of the great recession. A longitudinal cohort study from 2001 to 2015

Abstract: Background In Europe, one of the most consistent findings is that of migrant mortality advantage in high-income countries. Furthermore, the literature shows that economic shocks, which bring worse health outcomes, can severely affect the most disadvantaged individuals. We analyse differences and changes in all-cause mortality between Italians and migrants residing in Rome before, during, and in the aftermath of the Great Recession (2001–2015) by birth-cohort. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Internal migration was likely the most powerful factor discriminating growing from declining cities (e.g., Gavalas et al, 2014). At the same time, the lower elasticity of the natural component to external shocks and the slowing down of international migrations during COVID-19 pandemics may have consolidated such divides (Trappolini et al, 2001). These results document the urgent need to strengthen the self-restraining capacity of Southern Italian territories, by increasing their attractiveness (and permeability) to international migration flows.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Internal migration was likely the most powerful factor discriminating growing from declining cities (e.g., Gavalas et al, 2014). At the same time, the lower elasticity of the natural component to external shocks and the slowing down of international migrations during COVID-19 pandemics may have consolidated such divides (Trappolini et al, 2001). These results document the urgent need to strengthen the self-restraining capacity of Southern Italian territories, by increasing their attractiveness (and permeability) to international migration flows.…”
Section: Discussionmentioning
confidence: 90%
“…Examples can be found for Rome and Naples (Benassi et al, 2019b), Palermo (Busetta et al, 2016), Milan (Rimoldi & Terzera, 2017) and Catania (Mazza & Punzo, 2016) and for some of the main Italian urban contexts (Bitonti et al, 2023). Crisci (2010), Salvati and Carlucci (2014) and Trappolini et al (2021) provided specific contributions about demography, urban transformations, and differential mortality between foreigners and Italians in Rome. Strozza et al (2014b) focused on the demography and reproductive behaviors characteristic of Naples' neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…Migrants were operationally defined as people living in Italy but born abroad and were further classified according to their country of birth as follows: 1) migrants from High Migratory Pressure Countries (HMPCs: Central-Eastern Europe, Africa, Asia -except for Israel and Japan-, and Latin America); and 2) migrants from Highly Developed Countries (HDCs: North America, Europe— except for Central and Eastern Europe, Oceania, Israel, and Japan) [ 21, 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the number of migrants with cognitive disturbances referred to dedicated healthcare facilities (e.g., memory clinics) has been documented in some European countries [8][9][10]. However, recent surveys have shown that these services are still only partially prepared to manage dementia in patients with a history of migration and that several gaps and 2) migrants from Highly Developed Countries (HDCs: North America, Europe-except for Central and Eastern Europe, Oceania, Israel, and Japan) [21,22].…”
Section: Introductionmentioning
confidence: 99%